Mode I creep fracture of rubber-like adhesive joints at constant crack driving force. (March 2022) - Schrader, Peer; Schmandt, Christopher; Marzi, Stephan
Abstract: This work contributes to the description of time-dependent mechanical mode I creep fracture of viscoelastic adhesive joints under pure peel loading at finite deformations. The focus is on the dependency of crack resistance and resulting crack propagation rate on the forming of minor cracks beside the macroscopic major crack tip. In this work, Double Cantilever Beam tests were carried out at polyurethane-based flexible adhesive joints. The experiments were externally controlled on a constant J -integral, which was calculated in-situ from measured data to obtain a constant crack driving force and a statically loaded crack tip, respectively. The resulting creep crack propagation was investigated using two cameras targeting both sides of the specimen. With help of image processing and the beam compliance method, crack extension and crack propagation rate were determined. The respective results were used to draw comparisons between these two methods. The slight difference between the methods was attributed to the appearance of minor cracks, which seemed to reduce the stress intensity at the macroscopic crack tip, yielding a lower crack propagation rate. Highlights: Creep fracture under constant J -integral is investigated using DCB tests. Adhesive shows significant material scatter during creep fracture. Comparison between optical and compliance-based crack extension measurement. Stress intensity at major crack tip is influenced by forming of minor cracks. Crack propagation rate correlates with amount of minor cracks.